Outcomes After Minimally-invasive Versus Open Pancreatoduodenectomy: A Pan-European Propensity Score Matched Study. Issue 2 (February 2020) - Klompmaker, Sjors; van Hilst, Jony; Wellner, Ulrich F.; Busch, Olivier R.; Coratti, Andrea; D'Hondt, Mathieu; Dokmak, Safi; Festen, Sebastiaan; Kerem, Mustafa; Khatkov, Igor; Lips, Daan J.; Lombardo, Carlo; et al.
Abstract : Objective: To assess short-term outcomes after minimally invasive (laparoscopic, robot-assisted, and hybrid) pancreatoduodenectomy (MIPD) versus open pancreatoduodenectomy (OPD) among European centers. Background: Current evidence on MIPD is based on national registries or single expert centers. International, matched studies comparing outcomes for MIPD and OPD are lacking. Methods: Retrospective propensity score matched study comparing MIPD in 14 centers (7 countries) performing ≥10 MIPDs annually (2012–2017) versus OPD in 53 German/Dutch surgical registry centers performing ≥10 OPDs annually (2014–2017). Primary outcome was 30-day major morbidity (Clavien-Dindo ≥3). Results: Of 4220 patients, 729/730 MIPDs (412 laparoscopic, 184 robot-assisted, and 130 hybrid) were matched to 729 OPDs. Median annual case-volume was 19 MIPDs (interquartile range, IQR 13–22), including the first MIPDs performed in 10/14 centers, and 31 OPDs (IQR 21–38). Major morbidity (28% vs 30%, P = 0.526), mortality (4.0% vs 3.3%, P = 0.576), percutaneous drainage (12% vs 12%, P = 0.809), reoperation (11% vs 13%, P = 0.329), and hospital stay (mean 17 vs 17 days, P > 0.99) were comparable between MIPD and OPD. Grade-B/C postoperative pancreatic fistula (POPF) (23% vs 13%, P < 0.001) occurred more frequently after MIPD. Single-row pancreatojejunostomy was associated with POPF in MIPD (odds ratio, OR 2.95, P < 0.001), but not in OPD. Laparoscopic, robot-assisted, and hybrid MIPD had comparable major morbidity (27% vs 27% vs 35%), POPF (24% vs 19% vs 25%), and mortality (2.9% vs 5.2% vs 5.4%), with a fewer conversions in robot-assisted- versus laparoscopic MIPD (5% vs 26%, P < 0.001). Conclusions: In the early experience of 14 European centers performing ≥10 MIPDs annually, no differences were found in major morbidity, mortality, and hospital stay between MIPD and OPD. The high rates of POPF and conversion, and the lack of superior outcomes (ie, hospital stay, morbidity) could indicate that more experience and higher annual MIPD volumes are needed. Abstract : Supplemental Digital Content is available in the text